Governance, identity and freedom in Christian-inspired universities - Sánchez-Tabernero, Alfonso (Church, Communication and Culture, 2024)
This article examines how Christian-inspired universities can harmonize coherence with their identity and respect for the freedom of their professors and students. For nine centuries, higher education institutions have faced this challenge for many reasons, including the changing historical context. Various ways of dealing with it have been implemented. Our research identifies the different models chosen and describes their advantages and disadvantages. The literature review and the study of each strategic option allow us to identify the fact that institutions that establish close links between identity and their personnel policies, especially in the hiring of professors, better fulfill their mission. It also shows that respecting freedom does not require a position of neutrality but rather a characteristic attitude of the Christian message: the determination not to impose one’s own principles to the detriment of others’ freedom.